PELATIHAN PENGGUNAAN SCAFFOLDING TALK DALAM PENGEMBANGAN INSTRUKSI PEMBELAJARAN BAHASA INGGRIS BAGI GURU PAUD INTI KOTA BENGKULU - wisma yunita; Gita Mutiara Hati; Mei Hardiah (Universitas Bengkulu, 2020)
This paper aims to discuss the training on the use of scaffolding talk in developing English language learning instruction for kindergarten teachers of Bengkulu City. The purpose of the training was to enhance the quality of the kindergarten teachers’ professional development.Followed by 20 kindergarten teachers of English, the training used the inductive participative training method was held in PAUD Intan Insani in Muara Bangkahulu of Bengkulu city on August 3, 2019. The training consisted of three phases: presenting the training materials, developing lesson plans, and practicing using the lesson plans in the classroom. This training was also the application of the books of Kiddos: An Integrated, Communicative and Character-based Material for Kindergarten Students, the outcome of the national research grant in 2005-2016. In this training, the teachers were trained to use the scaffolding talk in developing the instruction for learning English. The result show that the teachers are able to develop the lesson plans based on the chosen topics in the books but there is no video of the teaching practices in the classroom were submitted by the teachers yet. It could probably caused by many administrative tasks and activities they have to fulfil at schools. In addition, there is also the tendency among the teachers that they prefer a short training instead of the one which take three phases and long time to finish. Therefore, it is suggested to conduct a short training which takes one short time only and has not had many phases to be fulfilled.